Numerical modeling of an uncofined aquifer dewatering and a soil vapor extraction system: a case study - Çiftçi, Emin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Contamination of soil and groundwater with volatile organic compounds has become a serious environmental issue. Soil vapor extraction (SVE) can be considered as one of the most commonly utilized techniques to remove these organic compounds from the soil. A soil vapor extraction system operates on the basis two main processes; volatilization of the residual organic compounds and transport of the organic vapor in the unsaturated zone. In this study a numerical model is developed for simulating soil vapor extraction process and the developed model is implemented for a case study. A gasoline station site, contaminated with four different volatile organic compounds, is the subject of the case study. Another dimension of this case study is the ongoing metro tunnel construction work executed underneath that gas station. The construction work is being executed at a level below groundwater table, therefore, due to leakage through tunnel walls the groundwater table is expected to drop with time. The impact of tunnels on the groundwater table is investigated in this work. The transient groundwater flow equation, derived by combining continuity equation with Darcy’s approach, is utilized while unconfined aquifer dewatering is being modeled. The developed numerical model for soil vapor extraction is based on solving vapor flow and advective-diffusive vapor transport equations successively. For both models, finite difference techniques are implemented. The aquifer dewatering simulation, performed over a four-month period, indicates that, at some locations the groundwater table drops to the level of the tunnels. With the soil vapor extraction simulation 5% of the organic mass is found to be removed from the soil after an extraction period of one month.
Keywords: Soil vapor extraction.